Tension pneumothorax in a patient with Covid-19 pneumonia initially misdiagnosed as volvulus - Yang, James; Trivedi, Aakash; Zuberi, Jamshed (Journal of the Pakistan Medical Association, 2023)
Tension pneumothorax is a condition that can present with a myriad of symptoms, including chest pain, shortness of breath, rapid breathing, and tachycardia. If left untreated, these signs and symptoms can progress to shock causing haemodynamic collapse and even death. At times, it may be difficult to identify tension pneumothorax. We present the case of a 59-year-old male with a prolonged initial hospital course that eventually led to a diagnosis of tension pneumothorax with the use of CT scans rather than traditional X-rays. This case reinforces the idea that clinicians should have a wide differential diagnosis in mind when dealing with vague symptoms and should not hesitate to use different diagnostic modalities to help confirm a diagnosis. Keywords: Pneumothorax, Intestinal volvulus, Covid-19, Pulmonary fibrosis, Pneumoperitoneum.